Studi Kasus Dari Perubahan Manajemen Operasional Dalam Proses Rekrutmen Tenaga Kerja Selama Masa Pandemi di Bank XYZ - Amin Sadiqin (PUTRA JAWA PUBLISHER, 2022)
The Covid-19 pandemic is expected to weaken the banking sector in Indonesia. Thus, bank companies that want to survive must face these changes with their respective strategies. One of these strategies is to look for superior and qualified prospective employees. This study was conducted using a qualitative approach with descriptive data analysis. Data collection is done directly through the interview method. The results of the study stated that during the pandemic the recruitment process at Bank XYZ was almost entirely online-based with the stages of file selection, introduction through zoom meetings, initial interviews, psychological tests, focus group discussions, presentations, final interviews, and medical check-ups. Obstacles to the recruitment process during a pandemic that often occur are such as the number of applicants entering for registration that is not in line with the validity of the incoming data, during FGDs and interviews sometimes they are interrupted due to network constraints and the possibility of fraud. The advantages of the online recruitment process include a wider reach of the labor market, cheaper operational costs for both organizers and recruiting participants and more flexible implementation times that can be done anywhere.